Comparative clinicopathological and outcome analysis of differentiated thyroid cancer in Saudi patients aged below 60 years and above 60 years - AL-Qahtani KH (Dove Medical Press, 2016)
Khalid Hussain AL-Qahtani,1 Mutahir A Tunio,2 Mushabbab Al Asiri,2 Yasser Bayoumi,3 Ali Balbaid,2 Naji J Aljohani,4 Hanadi Fatani5 1Department of Otolaryngology-Head & Neck Surgery, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Department of Radiation Oncology, Comprehensive Cancer Center, King Fahad Medical City, Riyadh, Saudi Arabia; 3Department of Radiation Oncology, NCI, Cairo University, Cairo, Egypt; 4Department of Endocrinology and Thyroid Oncology, 5Histopathology, Comprehensive Cancer Center, King Fahad Medical City, Riyadh, Saudi Arabia Introduction: The aim of this study was to evaluate the treatment outcomes of differentiated thyroid cancer in Saudi patients aged above 60 years. Materials and methods: Comparative analysis was performed in 252 patients aged 46–60 years (Group A) and 118 patients aged above 60 years (Group B), who had thyroidectomy, radioactive iodine-131, and thyroid-stimulating hormone suppression therapy between July 2000 and December 2012. Different clinicopathological features, treatment, complications, disease-free survival, and overall survival rates were compared. Results: Mean age of patients in Group A was 51.9 years (range: 46–60), and mean age of those in Group B was 68.6 years (range: 62–97). Group B patients had higher positive lymph nodes (43.2%), P=0.011. The frequency of extrathyroidal extension, multifocality, and lymphovascular space invasion was seen more in Group B than in Group A. Postsurgical complications (permanent hypoparathyroidism, bleeding, and wound infections) were also seen more in Group B (P=0.043, P=0.011, and P=0.021, respectively). Group B patients experienced more locoregional recurrences (11.0%, P=0.025); similarly, more distant metastases were observed in Group B (15.3%, P=0.003). The 10-year disease-free survival rates were 87.6% in Group A and 70.8% in Group B (P<0.0001). Conclusion: Differentiated thyroid cancer in patients aged above 60 years are more aggressive biologically and associated with a worse prognosis, and the morbidity is significantly high as compared to patients aged below 60 years. Keywords: differentiated thyroid cancers, patients aged above 45 years, aged above 60 years, clinicopathological characteristics, treatment outcomes, elderly patients, aged below 60 years, comparative analysis